Abnormal Recrystallization Behavior of the Cold‐Rolled AlZnMgZr (7046A) Sheets during Annealing. Issue 1 (26th July 2021) - Huang, Jiwu; Xu, Chenglong; Jiang, Fuqing; Jiang, Yingge
Abstract : The recrystallization behavior and microstructures' evolution of cold‐rolled AlZnMgZr (7046A) sheets with various annealing treatments are investigated. Compared with the conventional hardness versus annealing temperature curves, the abnormal hardening occurs above 375 °C, which triggers the contemplation about abnormal recrystallization behavior and abnormal hardening behavior herein. In accordance with texture evolution with diverse annealing temperatures or time, recovery and recrystallization processes are more sensitive to temperature than holding time, and the rolling texture also transforms into recrystallization texture at 350–375 °C. Afterward, microstructure analysis and the recovery and recrystallization theory are combined to obtain information about the dislocation density, the grain features, and the solid‐solution ability, explaining the annealing‐induced hardening phenomenon. In addition, the recovery process means that the dislocations are consumed and subgrains with low misorientation angle are transformed into subgrains with high misorientation angle, whereas the high‐angle subgrains are transformed into recrystallized grains during the recrystallization process. Combined with the grain distribution and abnormal hardness evolution, the abnormal recrystallization behavior is determined to occur at 375 °C. Due to poor thermal activation, recrystallization occurs preferentially in favorable sites, and some grains grow preferentially, resulting in abnormal recrystallization behavior. Abstract : The abnormal recrystallization behavior of a cold rolled AlZnMgZr (7046 A) alloy is reported. Experimental results show that the alloy's recrystallization temperature is ≈375 °C, and the lowest hardness value is obtained. Above 375 °C, the hardness increases with the increase in annealing temperature. The underlying static recovery and static recrystallization behavior of alloys are discussed.